Antibiotic and anti-quorum sensing activity of lysates from bioluminescent symbiotic bacteria from selected marine and freshwater organisms - Angeles, Roja Guia M (Archīum Ateneo, 2015)
In this study, 13 bioluminescent bacteria designated here as strains ADMU-UE-01 to 13, were isolated from marine and freshwater hosts. Six (6) pure cultures were subsequently obtained and screened, five (5) of which were from marine organisms, specifically BLB-ADMU-UE-01 (Johnius belangerii/ croaker), BLB-ADMU-UE-02 (Sillago analis/ golden-lined sillago), BLB-ADMU-UE-06 (Variola louti/ lapu-lapu), BLB-ADMU-UE-10 (Strombus variabilis/ variable conch ), BLB-ADMU-UE-12 (Cistopus indicus/ octopus) and only one (1) from a freshwater organism, BLB-ADMU-UE-04 (Chanos chanos/ milkfish), yielding Membrane Fraction (MF) with anti-quorum sensing activity against Pseudomonas aeruginosa based on the statistical results (p < 0.05). This study also indicated that the MF of the strain BLB ADMU-UE-10 has significant difference (p < 0.05) from the 0.15 mg/mL caffeine (positive control), showing that it has a very high anti-quorum sensing potential. Despite the differences in their hosts, the bacterial isolates shared evolutionary relationship with commonly known bioluminescent genera, using their respective 16S rRNA gene sequences; the BLB-ADMU-UE-01, BLB-ADMU-UE-02, BLB-ADMU-UE-04, BLB-ADMU-UE-06, and BLB-ADMU-UE-12 belonged to the genus Photobacterium (P. leiognathi and P. mandapamensis, 99-100% identity) while the BLB-ADMU-UE-05 and BLB-ADMU-UE-10 belonged to genus Vibrio (V. harveyi and V. campbelli, 99% identity).